Уменьшение потерь энергии в коммунальных Smart Grid сетях за счет перехода от однофазных к трехфазным системам электроснабжения - Жемеров, Георгий Георгиевич; Лобач, Игорь Олегович (НТУ "ХПИ", 2014)
Получены аналитические зависимости показателей эффективности перехода от однофазных к трехфазным системам электроснабжения – мощности потерь энергии и расхода меди.

Analytical dependences of such efficiency indices as energy loss power and copper consumption under transition from single-phase power distribution systems to three-phase ones are obtained.
Energy loss reduction in Smart Grid utilities for account of transition from single-phase to three-phasepower distribution systems
Keywords: расход меди; коммунальные потребители электроэнергии; генератор; частота; energy loss; copper consumption; power distribution system; Smart Grid